Pengaruh Dimensi Kualitas Pelayanan Dan Literasi Keuangan Terhadap Kepuasan Nasabah : (Studi Pada PT. Bank Rakyat Indonesia (persero)Tbk Kantor Cabang Jambi) - Pramita hadi, Anggun; Agustian, Efandri; Mulyani, Sri (Fakultas Hukum dan Ekonomi Bisnis, 2023)
This study aims to analyze the extent of the influence of financial literacy and service quality on increasing customer satisfaction. This research uses a quantitative approach with a sample of 100 respondents who are internal and external customers at Bri Kanca Jambi. Data obtained by distributing questionnaire links to respondents using google form. The data analysis technique used is Associative Analysis and Simultaneous Test. The results of the research analysis showed that financial literacy and service quality have a positive and significant effect on customer satisfaction. Simultaneous Test results show that financial literacy has a positive and significant effect on customer satisfaction as the dependent variable. Service quality has a positive and significant effect on customer satisfaction as the dependent variable. It is expected that every financial institution, especially Bank BRI Kanca Jambi, can improve its service quality so that it can increase feelings of interest and customer satisfaction.